Mastery learning in CS1: a longitudinal study during and post-pandemic - Vasa Buraphadeja; Vilasinee Srisarkun (Discover Education)
Abstract This study investigates the implementation and impact of mastery learning in a computer science course, particularly during the transition from traditional teaching methods to mastery learning amidst the COVID-19 pandemic. Employing a longitudinal research methodology, the study integrates a multi-faceted data collection approach, including student feedback, focus group interviews, and a comparative analysis of learning outcomes before and after the implementation of mastery learning. The findings reveal insights into the challenges of mastery learning, highlighting its potential to enhance student engagement and cater to diverse learning needs, while also noting the necessity of balancing innovative approaches with traditional methods. The study contributes to the growing body of literature on pedagogical strategies in computer science education by providing empirical evidence on the efficacy of mastery learning. The research also offers valuable implications for future instructional strategies, aiming to enhance the learning experience in computer science and potentially influence broader educational practices.